Blood pressure response to renal denervation is correlated with baseline blood pressure variability: a patient-level meta-analysis - Persu, Alexandre; Gordin, Daniel; Jacobs, Lotte; Thijs, Lutgarde; Bots, Michiel L; Spiering, Wilko; Miroslawska, Atena; Spaak, Jonas; Rosa, Ján; de Jong, Mark R; Berra, Elena; Fadl Elmula, Fadl Elmula M; et al. (Journal of hypertension, 2018)
BACKGROUND: Sympathetic tone is one of the main determinants of blood pressure (BP) variability and treatment-resistant hypertension. The aim of our study was to assess changes in BP variability after renal denervation (RDN). In addition, on an exploratory basis, we investigated whether baseline BP variability predicted the BP changes after RDN. METHODS: We analyzed 24-h BP recordings obtained at baseline and 6 months after RDN in 167 treatment-resistant hypertension patients (40% women; age, 56.7 years; mean 24-h BP, 152/90 mmHg) recruited at 11 expert centers. BP variability was assessed by weighted SD [SD over time weighted for the time interval between consecutive readings (SDiw)], average real variability (ARV), coefficient of variation, and variability independent of the mean (VIM). RESULTS: Mean office and 24-h BP fell by 15.4/6.6 and 5.5/3.7 mmHg, respectively (P < 0.001). In multivariable-adjusted analyses, systolic/diastolic SDiw and VIM for 24-h SBP/DBP decreased by 1.18/0.63 mmHg (P ≤ 0.01) and 0.86/0.42 mmHg (P ≤ 0.05), respectively, whereas no significant changes in ARV or coefficient of variation occurred. Furthermore, baseline SDiw (P = 0.0006), ARV (P = 0.01), and VIM (P = 0.04) predicted the decrease in 24-h DBP but not 24-h SBP after RDN. CONCLUSION: RDN was associated with a decrease in BP variability independent of the BP level, suggesting that responders may derive benefits from the reduction in BP variability as well. Furthermore, baseline DBP variability estimates significantly correlated with mean DBP decrease after RDN. If confirmed in younger patients with less arterial damage, in the absence of the confounding effect of drugs and drug adherence, baseline BP variability may prove a good predictor of BP response to RDN.
Keywords: Kidney; hypertenze; Female; Europe; výsledek terapie; ženské pohlaví; lidé; Sympathectomy; Evropa; Treatment Outcome; krevní tlak; Hypertension; sympatektomie; Male; Blood Pressure Determination; měření krevního tlaku; lidé středního věku; mužské pohlaví; Blood Pressure; ledviny; Middle Aged; Humans